'Empowering Online ESL Learners': Reflections on the Experience of Developing an Existing Undergraduate Course from a Classroom Based to a Predominantly Network-Based Environment - Noakes, Nick (Proceedings of the International Conference on Networked Learning, 2000)
This project focused on the design and delivery of an existing elective course in Advanced Reading and Writing in English for ESL learners for final-year BBA undergraduates at the Hong Kong University of Science and Technology (HKUST). I am the curriculum designer, materials writer and the course coordinator for this course (LANG 304 – see http://Jc.ust.hk/-coun;cs/304/ for the course description and objectives).